Am I Expected to Be Ethical? A Role-Definition Perspective of Ethical Leadership and Unethical Behavior - Paterson,Ted; Huang,Lei (Journal of Management, 2019)
Prior studies have demonstrated that leaders’ ethical behaviors have an impact on followers’ unethical behaviors and yet the explanatory mechanisms in this relationship have not been fully explored. To further explicate the relationship between ethical leadership and unethical employee behavior, we adopted a role-based perspective and introduced the concept of perceived ethical role breadth. That is, we explored the impact that leaders’ actions and voice behaviors have on in-role versus extra-role perceptions of employees as they relate to ethical behavior and the impact, in turn, on unethical behavior. In a field study involving 394 employees and 68 supervisors and a randomized experiment conducted with 121 working professionals we find that, as predicted, leaders’ behaviors and voice have a significant influence on perceived ethical role breadth and that these role breadth perceptions impact unethical behavior. Based on our empirical findings, we describe the implications, limitations, and future directions relevant to this study.
Keywords: Management